Komparasi Kinerja Keuangan Perbankan Konvensional Dan Perbankan Syariah - . Suripto (SOSIALITA, 2010)
Performance of bank was measured using CAMEL (Capital, Assets, Management, Equity Liquidity) approach, which was generally used to identify level of health of a bank. In this research, performance of the bank was measured based on the five aspects: capital adequacy, asset quality, management, earning and liquidity. This research was aimed to know difference of the financial performance of the conventional banking and the syariah banking. Financial measured by using ratios: ratio of capital to asset deliberated by according to risk, ratio of earning asset which classified to earning asset (KAP. I), ratio of allowance for possible earning losses to classified earning asset ( KAP.II), ratio of net operating income to operating income (NPM) representing proxy from management, ratio of profit before interest and tax to total asset ( ROA), ratio of operating expenses to operating income (BOPO), ratio of current assets to current liabilities and ratio of loan to deposit (LDR). This research use the saturated simple, that all bank of state of the public ownerships (BUMN) and bank of the Muamalat Indonesia, by using data of the secondary publicized by the Bank Indonesia each of semester, between period 1999 - 2003. The analysis instruments used was Multivariate Discriminant Analysis ( MDA). Results of this research indicate that the CAMEL approach can determine banking financial performance. Pursuant to statistical test really there was financial performance difference between conventional banking and syariah banking, where conventional banking have better finance performance from syariah banking . This research found that asset quality (KAP.I), LDR and ROA, significantly differentiate conventional banking finance performance and syariah banking, in which the KAP. I was the most dominant.